The cultural power metric: Toward a reputational analysis of China’s soft power in the Asia-Pacific - Yecies, B.; Keane, Michael; Yu, H.; Zhao, E.J.; Zhong, P.Y.; Leong, S.; Wu, Huan (2019)
The advent of new media technologies has changed how people watch, engage with, and share digital media. Conventionally, audiences were surveyed selectively, and the results were collated by professional agencies and often kept confidential. However, the conspicuous ratings given to media and cultural products outside their country of origin and their very public success and failure raises questions about the validity of such methods, particularly at a time when media and cultural products are used as proxies for cultural “soft power.” This term, first used by Joseph Nye in a political context, evokes reputational impact: a particular nation’s cultural and media products can “go global” if they prove sufficiently popular, reflecting positively on the originating nation. This article examines the various methods used to evaluate China’s “cultural power.” It notes the current weighting given to the humanities and social sciences. By applying some basic big data analysis and machine-learning techniques, the authors build on previous studies by offering new insights into the rise of “Digital China” and China’s digital and Internet trailblazers. The authors consider two major international metrics, as well as China’s early experimental attempts at devising its own standard, before introducing an alternative model, the cultural power metric.